Langfristige Herausforderungen für die Verkehrsinfrastruktur in Deutschland - Georg Hirte; Stefan Tscharaktschiew (Wirtschaftsdienst, 2023)
– We discuss future challenges to road transport infrastructure. These are related to maintenance, autonomous transport and the fi-nancing of infrastructure. We state that maintenance investments are mainly relevant and necessary to avoid a strong reduction in accessibility;autonomous driving will not allow for the reduction in infrastructure investment. A share of revenue from a kilometer tax and city charges will beused to finance road infrastructure and cross-finance other infrastructure.
Keywords: H54; R42; R48; 330